(untitled) (Teología, 2017)
The article proposes a theological deepening to support the ecological conversion to which Pope Francis invites us in Laudato Si’. According to the Bible and its reception in Israel and the Church, the world is a temple. Such statement implies understanding salvation history in terms of a cosmic liturgy, which begins and ends in the Holy Trinity.